Visual frame analysis of the UKIP leave campaigns 'Turkish migrant' Brexit visuals - Erisen, Hanife; Ersoy, Metin (Routledge Journals, Taylor & Francis Ltd, 2025)
The lead up to the 23 June 2016 democratic divorce of the United Kingdom from the European Union observed rigorous campaigning from the 'Leave' and 'Remain' spectrums. Immigration was high on the agenda, with UKIP's leave campaign commissioning seven visuals focusing on migration from Turkey, with this anti-immigration rhetoric receiving much criticism. This study analysed these visuals by performing a semiotic and visual frame analysis. The findings present important indications of how politicians utilize existing connotations and 'othering' ideologies to influence political decisions, and the messages in accordance with the socio-political climate prevalent at the time. It was found that the visuals relied heavily on connotations appropriated upon the Turkish identity, and their previously invested-in self-other ideologies, enabling the visuals to transcend a greater message. Simultaneously, pre-existing antagonism connected to immigration was also utilized within a setting of political distrust. The rhetoric promoted basing Brexit on Turkey's entrance to the Union, omitting the Union from the equation and question.
Keywords: Brexit; Turkey; immigration; visual frame analysis; United Kingdom; orientalism